PERAN PERHATIAN ORANG TUA TERHADAP PROSES BELAJAR ANAK DARI RUMAH PADA MASA PANDEMI COVID-19 - Ummu Jauharin Farda; Anas Rohman; Achmad Mustofa (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2021)
AbstracThe role of parental attention in supervising the child's learning process at home during the Covid-19 pandemic, parents become teachers automatically, accompany children's learning, help explain subject matter to children, provide means of accessing learning from home such as laptops, smart phones and others. , facilitate internet access. Inhibiting factors in the child's learning process at home during the Covid-19 pandemic include: limited internet access or quotas, not having a lektop or gaadged, lack of parental attention, difficulty in understanding lessons due to the online learning process, while supporting factors include the availability of tools online learning, the existence of student interest in the online learning process, the motivation of parents and the healthy condition of students. This research method is a field research or field research. Research Subjects, the subjects to be studied are school children in RT 002 RW 001, Sekayu Village, Semarang City. The object of this research will be carried out in RT 002 RW 001 Sekayu Village, Semarang City. Analysis of the data used is non-statistical analysis but with qualitative analysis. The condition of the Covid-19 pandemic in RT 002 RW 001, Sekayu Village, Semarang City, from an economic point of view, is not very influential but from an educational perspective it shows that it is very influential because of the readiness of schools and students to participate in online learning.Keywords: Parental Attention, Learning Process, Covid pandemic AbstrakPeran perhatian orang tua dalam mengawasi proses belajar anak di rumah pada masa pandemi Covid-19 orang tua menjadi guru secara otomatis, menemani belajar anak, membantu menjelaskan materi pelajaran kepada anak, memberikan sarana mengakses belajar dari rumah seperti laptop, smart phon dan lain-lain, menfasilitasi akses internet. Faktor penghambat dalam terhadap proses belajar anak di rumah pada masa pandemi Covid-19 diantaranya: keterbatasan akses internet atau kuota, tidak memiliki lektop atau gaadged, kurangnya Perhatian orang tua, kesulitan dalam memahami pelajaran karena proses belajar daring, sedangkan  faktor pendukung di antranya tersedianya alat belajar daring, adanya minat siswa dalam proses belajar daring , adanya motivasi dari orang tua dan kondisi siswa yang sehat. Metode penelitian  ini merupakan riset lapangan atau field research. Subjek Penelitian, Subjek yang akan diteliti adalah anak-anak Sekolah di RT 002 RW 001 Kelurahan Sekayu Kota Semarang.Objek penelitian ini akan dilaksanakan di RT 002 RW 001 Kelurahan Sekayu Kota Semarang. Analisis data yang digunakan adalah analisis non statistik melainkan dengan analisis kualitatif. Kondisi pandemi Covid-19 di RT 002 RW 001 Kelurahan Sekayu Kota Semarang dilihat dari sisi ekonomi tidak begitu berpengaruh tetapi di lihat dari segi pendidikan ini menunjukkan sangat mempengaruhi karena kesiapan dari sekolah maupun dari siswa untuk mengikuti pembelajaran daring.Kata Kunci : Perhatian Orang Tua, Proses Belajar, Pandemi covid